Sport-related cutaneous infections: A narrative review - Santoso, B. N.; Korman, A. M.; Bechtel, M. A.; Baria, M. R. (Clinical Journal of Sport Medicine, 2025)
Bacterial and viral cutaneous infections pose a great risk of serious complications in combat athletes and contribute to a significant amount of time lost in practice and competition. Although these infections can be treated with standard antimicrobials, the rise in resistance of Staphylococcus aureus and dermatophytes calls for updated treatment recommendations. Methicillin-resistant S. aureus (MRSA) is becoming a highly prevalent culprit of impetigo, folliculitis, and cellulitis and must be managed correctly to eradicate infection effectively. In addition, the increased prevalence of tinea incognito and terbinafine-resistant Trichophyton tonsurans makes dermatophyte infections difficult to handle. Limited studies provide evidence for a nuanced approach when treating athletes who engage in weight cycling or rapid weight loss, but adjusted dosing and treatment guidelines remain important.